Financial welfare of families of Sunday market traders in bengkulu city In terms of sociodemographics: economy - Ramanda, Aprilia; Kamaludin, Kamaludin (Institute of Computer Science (IOCS), 2023)
This study was conducted to describe the welfare level of Sunday market traders in Bengkulu city as seen from the level of family finances, health quality, religiosity level and education level. This research uses a descriptive approach with the Spearman Rank correlation test method. Data collection techniques were carried out by interview, observation and questionnaire, through cluster purposive sampling method as many as 150 samples. The purpose of this research is to find out how the level of welfare of the trader's family and also the relationship between variables. The results show that the level of family finances, the quality of health, the level of religiosity and the level of education are interrelated with the level of welfare with a fairly positive coefficient. The relationship between the level of family finances and the level of welfare is 0.080 with a very low category. The relationship between the quality of health and the level of welfare is 0.270 with a low category, the level of religiosity with the level of welfare is 0.338 with a low category, while the quality of education with the level of welfare is 0.412 with a medium category.